An atypical case of Kawasaki disease with severe pneumonia in a neonate - Kawamura, Yoshiki; Miura, Hiroki; Saito, Kazuyoshi; Kanno, Takayuki; Yokoyama, Tadafumi; Aizawa, Yuta; Yoshikawa, Tetsushi (BMC pediatrics, 2022)
Kawasaki disease (KD) is an acute, febrile, systemic vasculitis of unknown etiology that primarily affects the coronary arteries and generally occurs at around 1 year of age. Although the diagnosis of KD is generally not difficult, it is challenging in cases of incomplete KD lacking characteristic clinical manifestations. The incidence of incomplete KD is higher in infants younger than 6 months of age. Pneumonia is an extremely rare complication of KD and can be misinterpreted as atypical pneumonia rather than KD. Herein, we report a neonate with atypical KD and severe pneumonia who required mechanical ventilation. Japanese one-month-old infant had only fever and rash on admission (day 1), and he was transferred to the intensive care unit for severe pneumonia on day 2. Although pneumonia improved following intensive care, he was diagnosed with KD on day 14 because of emerging typical clinical manifestations such as fever, bulbar nonexudative conjunctival injection, desquamation of the fingers, and coronary artery aneurysm. KD symptoms improved after three doses of intravenous immunoglobulin plus cyclosporine. However, small coronary aneurysms were present at the time of discharge. In a retrospective analysis, no pathogens were detected by multiplex real-time PCR in samples collected at admission, and the serum cytokine profile demonstrated prominent elevation of IL-6 as well as elevation of neopterin, sTNF-RI, and sTNF-RII, which suggested KD. The patient's entire clinical course, including the severe pneumonia, was caused by KD. As in this case, neonatal KD may exhibit atypical manifestations such as severe pneumonia requiring mechanical ventilation.